Phenotypic modulation of smooth muscle cells in lymphoedema. (9th March 2015) - Ogata, F.; Fujiu, K.; Koshima, I.; Nagai, R.; Manabe, I.
Summary Background Lymphoedema is a debilitating progressive condition that is frequently observed following cancer surgery and severely restricts quality of life. Although it is known that lymphatic dysfunction and obstruction underlie lymphoedema, the pathogenic mechanism is poorly understood. Smooth muscle cells (SMCs) play pivotal roles in the pathogenesis of various vascular diseases, including atherosclerosis. Objectives We analysed SMCs in lymphatic vessels from the lymphoedematous legs of 29 patients. Methods Expression of smooth muscle α‐actin (SMαA) and smooth muscle myosin heavy chain (SM‐MHC) isoforms SM1 and SM2 was investigated using immunohistochemistry. Results Compared with normal lymphatic vessels, all affected lymphatic vessels in chronic lymphoedema showed marked wall thickening. In addition to increases in the numbers of rows of SMαA+ SM1+ SMCs in the tunica media, SMCs were also observed in the subendothelial region (tunica intima). While most intimal and medial cells were positive for SMαA and SM1, staining for SM1 and particularly SM2, a marker of mature SMCs, progressively declined in lymphatic vessels in increasingly severe lymphoedema lesions. Consequently, the SM1+ and SM2+ cell fractions were significantly reduced in the tunica media and intima of lymphatic vessels. Conclusions These observations indicate that the lymphatic tunica media and tunica intima consist mainly of phenotypically modulated SMCs, and that SMCs play a key role in the development of lymphoedema.